Pengaruh Metode Discovery terhadap Pemahaman Konsep Matematika pada Kelas VII di SMP Negeri 2 Pasaman - Asmara, Lili; Aniswita, Aniswita; Rahmi, Ulva; Fitri, Haida (MASALIQ, 2025)
The background to the problem is student’s low understanding of mathematical concepts. This research aims to determine the significant influence of the discovery method on students' understanding of mathematical concepts in class VII at SMP Negeri 2 Pasaman for the 2023/2024 academic year. This type of research is pre-experimental with the research design The Static Group Comparison Design. The population in this study were all class VII students at SMP Negeri 2 Pasaman, totaling 84 students. The instrument in this research is a test of students' understanding of mathematical concepts. From the results of data analysis of students' mathematical concept understanding tests using the t-test, it was obtained that t_count = 2.622 and t_table = 1.676. Because t_count > t_table so H_0 is rejected and H_1 is accepted. For SPSS software testing at a real level of a = 0.05, sig = 0.012, meaning sig < a, so H_0 is also rejected. So it can be concluded that there is a significant influence of the discovery method on students' understanding of mathematical concepts in class VII at SMP Negeri 2 Pasaman for the 2023/2024 academic year.